Meningkatkan Daya Dukung Pondasi Tiang Pancang Gedung Baru Rumah Sakit Baptis Kediri Menggunakan Metode Mayerhoff - Lintang Ratnasari Satiti; Yosef Cahyo Setianto Poernomo; Sigit Winarto; Andri Dwi Cahyono (Kadiri University, 2021)
The foundation is an important part of the building structure because it functions as a support. The selection of this pile foundation has various considerations, namely the pile foundation can achieve the hardest soil bearing capacity, made with a manufacturing system, then the quality of the concrete can be guaranteed, the soil bearing capacity is not only obtained from the tip of the pile. Foundation planning needs to be well planned to support user safety and comfort. Pile foundation is one type of foundation chosen because it is more cost-effective and quality than other foundations. This study aims to plan the pile foundation for a new building at Baptist Hospital Kediri. The calculations carried out include calculating the load received by each column, the carrying capacity of a single pile permit, the dimensions and depth of the pile, as well as the required pile cap dimensions. Calculation of the pile foundation is carried out using the Mayerhoff method. The calculation results show that the load on the column area (K13) is 212.23.04 tons, the carrying capacity of the single pile permit (Qall) is 87509.33 kg and Quult is 218773.3 kg and the use of 4 piles on one pile with dimensions of 40 x 40 cm with a depth of 10.6 m, With these results can be used as a reference in the construction of a new building Baptist Hospital that is safe and able to withstand the load of the building.